Sonography of the median nerve in CMT1A, CMT2A, CMTX, and HNPP. Issue 3 (4th February 2013) - Schreiber, Stefanie; Oldag, Andreas; Kornblum, Cornelia; Kollewe, Katja; Kropf, Siegfried; Schoenfeld, Ariel; Feistner, Helmut; Jakubiczka, Sibylle; Kunz, Wolfram S.; Scherlach, Cordula; Tempelmann, Claus; Mawrin, Christian; et al.
<x xml:space="preserve">Abstract</x> Introduction: In this study we compare the ultrasound features in the median nerve in patients with different types of Charcot–Marie–Tooth (CMT) disease and hereditary neuropathies with liability to pressure palsies (HNPP) as a typical entrapment neuropathy. Methods: Median nerve ultrasound and conduction studies were performed in patients with CMT1A (n = 12), MFN2‐associated CMT2A (n = 7), CMTX (n = 5), and HNPP (n = 5), and in controls (n = 28). Results: Median nerve cross‐sectional area (CSA) was significantly increased in CMT1A, whereas, in axonal CMT2A, fascicle diameter (FD) was enlarged. CSA correlated with nerve conduction slowing in CMT1A and with axonal loss, as shown by motor and sensory nerve amplitudes in both CMT1A and CMT2A. A relatively low wrist‐to‐forearm‐ratio (WFR <0.8) or a relatively high WFR (>1.8) appeared to be unlikely in MFN2 and Cx32 mutations of CMT2A and CMTX, respectively. Conclusion: Differences in CSA, FD, and WFR of the median nerve can be helpful in defining subtypes of hereditary neuropathies. Muscle Nerve 47:385‐395, 2013